Exploring the household food-wasting behaviour A bibliometric review - Liu, Yang (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2025)
Despite plenty of research recently conducted, household food waste still has not been comprehensively investigated. In view of this, we systematically reviewed the literature on this topic (using VOSviewer), made content analyses and identified several issues in these studies. This study aims to provide an in-depth review on household food waste research by highlighting the research gaps. Our findings indicate that the recent studies on household food waste can be broadly categorised into three interconnected segments: definition of food waste, cause analysis of household food waste and strategies for reducing household food waste. It was found that targeted strategies could reduce food waste by up to 27.85% in some regions. In addition, intervention strategies reduced total household food waste and avoidable food waste by 31% and 30%, respectively, showing excellent performance. This review highlights the importance of targeted research on consumer behaviour and regional conditions in reducing household food waste, as well as the necessity of working out solutions to household food waste within a common interest community